2013
DOI: 10.1177/0300060513496172
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synergistic activity of colistin with tigecycline or β-lactam antibiotic/β-lactamase inhibitor combinations against carbapenem-resistant Acinetobacter baumannii

Abstract: Colistin combined with tigecycline, cefoperazone/sulbactam or piperacillin/tazobactam revealed synergistic effects in some carbapenem-resistant A. baumannii strains. These results, together with the shortage of treatment options and the risk of developing resistance to colistin, suggest that clinicians should use colistin combined with other antibiotics or β-lactamase inhibitors when treating carbapenem-resistant A. baumannii infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 33 publications
2
22
0
1
Order By: Relevance
“…Another reason is to provide a synergistic effect for the salvage therapy because of the debate about low penetration of the colistin into the lungs. According to other studies, imipenem, meropenem, sulbactam, rifampicin, and tigecycline were found to have synergistic effects with colistin [2,[23][24][25][26]. Clinical studies researching the effect of combination therapy with respect to clinical response, microbiological response, and mortality have been limited, and there is no consensus.…”
Section: Discussionmentioning
confidence: 99%
“…Another reason is to provide a synergistic effect for the salvage therapy because of the debate about low penetration of the colistin into the lungs. According to other studies, imipenem, meropenem, sulbactam, rifampicin, and tigecycline were found to have synergistic effects with colistin [2,[23][24][25][26]. Clinical studies researching the effect of combination therapy with respect to clinical response, microbiological response, and mortality have been limited, and there is no consensus.…”
Section: Discussionmentioning
confidence: 99%
“…After that, strips are aseptically removed and the second strip is deposited overlapping the first one. Finally, plates are incubated for 24 hours and MIC values are recorded (Karaoglan et al, 2013) (This method is referenced in Table 1 as 1+1 strip).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Synergy as ∑FIC≤0.5; indifference as 4≥∑FIC>0.5 and antagonism as ∑FIC>4 (Pankey andAshcraft, 2009, Tan, Ng, Tan andHuang, 2007), or 3. Synergy as ∑FIC≤0.5; indifference as 2≥∑FIC>0.5 and antagonism as ∑FIC≥2 (Karaoglan, Zer, Bosnak, Mete and Namiduru, 2013), or 4. Synergy as ∑FIC≤0.5; additive as 1≥∑FIC>0.5; indifference as 4>∑FIC>1 and antagonism as ∑FIC≥4 (Cetin, Tekeli, Ozseven, Us and Aridogan, 2013).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The time at risk, the period of time at risk for appearance of IR-MDRAB, is a very important confounding factor to be adjusted because the probability of appearance increases with the length of time (3). The best therapeutic approach for CRAB infection is to use colistin in combination with tigecycline or cefoperazone–sulbactam or piperacillin–tazobactam (38). …”
Section: Drug Resistance Exhibited By a Baumanniimentioning
confidence: 99%